Вибір комунікаційної стратегії на різних стадіях розвитку бренду як складова інформаційного потоку підприємства - Турчина (Побережна), Марія Петрівна; Бойко, Ірина Анатоліївна; Тур, Олеся Василівна (My University, 2023)
У сучасних умовах роботи особливу важливість одержує інформаційне забезпечення підприємства як передумова його ефективного функціонування. Ефективним засобом є застосування комунікацій, як системи підтримки інформаційної взаємодії підприємства з його внутрішнім і зовнішнім бізнес-середовищем. Керівництво підприємства має прагнути щоб комунікації були ефективні. В статті представлено основні типи комунікаційних стратегій, використання яких дозволяє покращити комунікаційну діяльність підприємства. Охарактеризовано етапи розробки комунікаційної стратегії та запропоновано комплекс дій на кожному етапі розробки для кожного типу комунікаційної стратегії. Розглянуто основні етапи формування та розвитку бренду. Для кожного з розглянутих етапів розвитку бренда запропоновано використання відповідної комунікаційної стратегії. n the modern terms of work the special importance is got by the dataware of enterprise as pre-condition of him effective functioning. Effective means is application of communications, as systems of support of informative cooperation of enterprise with his internal and external business-environment. Communications of subject of economic activity play an important role realization of strategic aims of enterprise. The report of the correctly set forth communicative reports of subject to his target groups forms favourable basis for activity in the system of economic relations, helps to secure support of public for defence of interests and reputation of subject of economic activity. On the modern stage of development of economy the question of determination of quality and efficiency of communications of enterprise gets up very important. Determination of correct strategic course is the most responsible business for an enterprise, as forms priorities of his activity on relatively long-term prospect. It is extremely important to walk up the That management of company self-weighted to the process of choice and realization of communication strategy, taking into account many internal and external factors and accenting attention on some from them. Today it is very difficult to attract attention business entities to the brands, that is why it will be them to search the methods of organization of reports to the consumers about itself and the products. On the basis of it the question of choice of communication strategy becomes very important on the different stages of development of brand. Not having regard to the far of scientific publications from this range of problems, to the choice of communication strategy on the different stages of development of brand as a constituent of dataflow of enterprise it remains not fully studied. It stipulated the theme of the article. The basic types of communication strategies, the use of that allows to improve of communication activity of enterprise, are presented in the article. Design of communication strategy times are described and the complex of operating offers on every design time for every type of communication strategy. The basic stages of forming and development of brand are considered. For each the use of corresponding of communication strategy offers of the considered stages of development of brand.
Keywords: кафедра економіки праці та менеджменту; кафедра маркетингу; комунікаційна стратегія; розробка комунікаційної стратегії; типи комунікаційних стратегій; бренд; життєвий цикл бренду; communication strategy; communication strategy development; types of communication strategies; brand; brand life cycle